Platelet-rich plasma attenuates the UPEC-induced cystitis via inhibiting MMP-2,9 activities and downregulation of NGF and VEGF in Canis Lupus Familiaris model - Ahmed I. Abdelgalil; Aya M. Yassin; Marwa S. Khattab; Elshymaa A. Abdelnaby; Sherif A. Marouf; Haithem A. Farghali; Ibrahim A. Emam (Scientific Reports, 2024)
Abstract One of the most prevalent disorders of the urinary system is urinary tract infection, which is mostly brought on by uropathogenic Escherichia coli (UPEC). The objective of this study was to evaluate the regenerative therapeutic and antibacterial efficacy of PRP for induced bacterial cystitis in dogs in comparison to conventional antibiotics. 25 healthy male mongrel dogs were divided into 5 groups (n = 5). Control negative group that received neither induced infection nor treatments. 20 dogs were randomized into 4 groups after two weeks of induction of UPEC cystitis into; Group 1 (control positive; G1) received weekly intravesicular instillation of sodium chloride 0.9%. Group 2 (syst/PRP; G2), treated with both systemic intramuscular antibiotic and weekly intravesicular instillation of PRP; Group 3 (PRP; G3), treated with weekly intravesicular instillation of PRP, and Group 4 (syst; G4) treated with an intramuscular systemic antibiotic. Animals were subjected to weekly clinical, ultrasonographic evaluation, urinary microbiological analysis, and redox status biomarkers estimation. Urinary matrix metalloproteinases (MMP-2, MMP-9) and urinary gene expression for platelet-derived growth factor -B (PDGF-B), nerve growth factor (NGF), and vascular endothelial growth factor (VEGF) were measured. At the end of the study, dogs were euthanized, and the bladder tissues were examined macroscopically, histologically, and immunohistochemically for NF-κB P65 and Cox-2. The PRP-treated group showed significant improvement for all the clinical, Doppler parameters, and the urinary redox status (p < 0.05). The urinary MMPs activity was significantly decreased in the PRP-treated group and the expression level of urinary NGF and VEGF were downregulated while PDGFB was significantly upregulated (p < 0.05). Meanwhile, the urinary viable cell count was significantly reduced in all treatments (P < 0.05). Gross examination of bladder tissue showed marked improvement for the PRP-treated group, expressed in the ...